Studies in Colombian Ensifera and adjacent countries: Gigagryllus, a new genus of giant field crickets (Orthoptera: Gryllidae) with comments on current Neotropical Gryllinae classification - Cadena-Castañeda, Oscar J.; García, Alexander García (Zootaxa, 2020)
Gigagryllus omayrae n. gen et n. sp., a new genus of giant field cricket, from the middle Magdalena of Colombia, more precisely from the department of Tolima, in the region of the Armero tragedy, for which this species is dedicated to the memory of Omayra Sanchez, a symbol of the most terrible natural tragedy that has occurred in the recent history of Colombia. Gigagryllus n. gen. is one of the largest genera in America, with a size similar to Titanogryllus, Megalogryllus and some species of Gryllita. The classification of the American Gryllinae is discussed, and a key to the American genera is provided. Besides, genera groups are proposed for the subtribe Brachytrupine (Gryllini) taxa, which differs from Old World genera. Geogryllus n. syn. and Rubrogryllus n. syn. are synonymized under Gryllita and Cophogryllus americanus is considered as nomen dubium, ruling out the presence of subtribe Cophogryllina in America.